Effect of Some Spice Essential Oils on the Stability of Frying Oils - Sandal Tanriverdi, Ebru; Tanriverdi1, al; Musa Özcan, Mehmet; Al Juhaimi, Fahad (Asian Journal of Chemistry, 2013)
In this study, peppers and potatoes were fried in olive and peanut oils. In order to evaluate the oxidative stability of frying oils, essential oils of sage, rosemary, thyme at the concentration of 0.3, 0.6, 0.9 and 1.2 %, separately and 0.01 % butylated hydroxytoluene were added into olive and peanut oils. Chemical properties of frying oils (free fatty acid %, peroxide value, DPPH, total phenolic and fatty acid composition) were determined after frying. Butylated hydroxytoluene showed the best effect on free fatty acid % and peroxide value of olive oils after frying of peppers and potatoes. Free fatty acid % values of frying oils of peppers and potatoes showed variation. The nearest values of oleic, linoleic and linolenic acid contents of frying olive oils of peppers and potatoes were determined with sample addition of butylated hydroxytoluene. Oleic, linoleic and linolenic acid contents of peanut oil with butylated hydroxytoluene and potato frying oil that addition of 0.3 % rosemary essential oil were determined to nearly the initial value of oil. These essential oils were also determined to show high radical scavenging effect. Rosemary essential oil was determined higher the radical scavenging effect and lower total phenolic compounds than thyme essential oils. There were not exact a relationship between radical scavenging effect and the amount of total phenolic compounds. The aim of current study is to establish to the effect of some spice essential oils on the stability of frying oils.